Health and social needs of waste pickers at Brgy. Calajunan, District of Mandurriao, Iloilo City - Ibabao, Rhodella A. (Danyag :the UPV journal of humanities and social sciences, 2004)
"The study brings attention to the pressing health and social dilemmas facing those at the lowest level of the waste economy, the waste pickers. Fifty-six respondents participated in the survey and general profiles were created to depict a typical life of a waste picker. The survey, non-participant observation and secondary analysis were used in data collection. Results showed that the decision in waste picking is generally driven by economic factors. Waste pickers have low educational attainment, live in generally poor social condition, and have limited access to basic social services. Their health and social situation prevent them from improving their economic status in life and put them at risk to all types of danger."